The impact of cranioplasty in cerebral blood flow and its correlation with clinical outcome in patients underwent decompressive craniectomy - Mah Jon , Kooi (2015)
Background Decompressive craniectomy are commonly use as the treatment for medically refractory intracranial hypertension. It is a common practice in Malaysia and worldwide, that patient will have subsequent reconstructive cranioplasty. Unexpected improvement in patient’s neurological status has been observed among patients that underwent cranioplasty procedure. Restoration of CBF hemodynamics is one of the factors said to affect patient’s clinical outcome postcranioplasty. Therefore, this study was conducted to determine the impact of cranioplasty on CBF and its correlation with clinical outcome in patients undergoing decompressive craniectomy. Objectives This study was done to evaluate the effect of cranioplasty on CBF with CT perfusion in patients with previous decompressive craniectomy undergoing cranioplasty. Besides that, the effect of cranioplasty on clinical outcome based on GOS, MMSE & FAB was also evaluated. This study also aimed to determine the correlation between post-cranioplasty CBF and clinical outcome Methodology A prospective observational study was done on patients who have underwent decompressive craniectomy for intracranial hypertension and requiring reconstructive cranioplasty at Hospital Sungai Buloh. This study was conducted between 1st September 2013 and 1st September 2014 and a total of 22 patients were included in this study. During admission, all patients had CT perfusion done to determine pre-cranioplasty CBF. Clinical outcome was assessed using GOS, MMSE and FAB. Subsequent, follow up was done at 6 weeks and 24 weeks post cranioplasty. At 6 weeks post cranioplasty follow up, a repeat CT perfusion scan and assessment of clinical outcome was performed. During the 24 weeks post-cranioplasty follow up, only clinical outcome was evaluated. Data entry and analysis was done using Statistical Package for Social Sciences (SPSS) version 12.0.1. Results The median value of the ipsilateral cortical CBF was 48.87 (IQR 25.05) ml/min/100g and 61.10 (IQR 31.65) ml/min/100g at pre-cranioplasty and 6 weeks post-cranioplasty respectively (p<0.001). Similarly for contralateral cortical CBF, which showed improvement from 60.55 (IQR 23.61) ml/min/100g to 71.84 (IQR 24.59) ml/min/100g at 6 weeks post-cranioplasty (p<0.001). No difference seen in the median value for GOS which was 4 at pre, 6 and 24 weeks post-cranioplasty with p=0.046 and p=0.014 respectively. Median value for MMSE showed significant difference with value of 22 (IQR 12.75), 25 (IQR 12.50) and 25.5 (IQR 13.00) at precranioplasty, 6 and 24 weeks post-cranioplasty respectively (p=0.001 and p<0.001). Median value for FAB was 12 (IQR 10.75) at pre-cranioplasty, 14.5 (IQR 11.35) at 6 weeks postcranioplasty and 15 (IQR 11.25) at 24 weeks post-cranioplasty. The difference at pre cranioplasty to 6 and 24 weeks post-cranioplasty was significant with p=0.002 and p=0.001 respectively. No significant correlation between CBF and clinical outcome (p>0.05). Conclusion Cranioplasty in the past is known as a surgical procedure that restore cranial defect to provide cerebral protection and cosmesis. In our present study, it suggests that cranioplasty can remarkably improve cortical perfusion for both the ipsilateral and contralateral hemisphere. Besides that, we also believe that cranioplasty has a therapeutic role in terms of clinical outcome improvement which was observed in our study. Even though, we are unable to establish a strong positive correlation between improved cerebral blood flow and clinical outcome, the results obtained so far may shed light on the significant role of cranioplasty on the improvement of cerebral perfusion and clinical outcome. This we hope will generate interest among future researchers to carry out multi-centered randomized trials which can analyze a larger number of patients to further draw a concrete conclusion to support our claim. Based on this study, we would like to propose that cranioplasty should be done to all patients with previous history of decompressive craniectomy to improve cerebral perfusion and clinical outcome as it also provides cerebral protection and cosmetic correction.